Ophthalmic Manifestation and Pathological Features in a Cohort of Patients With Linear Nevus Sebaceous Syndrome and Encephalocraniocutaneous Lipomatosis - Yan, Yan; Zhang, Siyi; Zhou, Henghua; Zhou, Yixiong; Fu, Yao (Frontiers in Pediatrics, 2021)
Purpose: This study aimed to figure out the association between ophthalmic and pathological features in patients with Linear Nevus Sebaceous Syndrome (LNSS) and in patients with Oculoectodermal Syndrome – Encephalocraniocutaneous Lipomatosis (OES-ECCL) . Methods: It is a retrospective, nonconsecutive, observational case series. Twenty-seven patients (12 with LNSS and 15 with OES-ECCL, 41 eyes) referred to the Department of Ophthalmology of the Shanghai Ninth People’s Hospital between 2000 and 2020 were included. The mean age of the study population for the first-time consult was 5.7 years, ranging from 3 months to 34 years. Clinical notes, pathological records, and imaging findings were reviewed in all the patients. Results: Fourteen (51.9%) cases showed bilateral ocular involvement. Epibulbar choristomas were seen in all the patients. All the lesions involved the conjunctiva and cornea simultaneously. Multiple lesions were observed in 12 eyes. Of the 14 excised lesions, 11 were found to be complex choristomas. Further, 24 (89%) patients had eyelid coloboma. Also, 13 patients (48%) were diagnosed with strabismus, and 12 patients (44%) had abnormal fundus imaging, including optic nerve hypoplasia. Conclusions: LNSS and OES-ECCL shared common ophthalmic features, including epibulbar choristomas with distinctive characteristics, eyelid coloboma, strabismus, and optic nerve hypoplasia. The complex choristoma was found to be associated with the diseases. These specific patterns can be diagnostic clues to distinguish them from other syndromes, such as craniofacial defects, and to remind ophthalmologists that such patients require additional dermatological and neurological examinations and referral. Moreover a thorough evaluation of ocular conditions is imperative for early interventions.